DISPUTE SETTLEMENT IN THE OMBUDSMAN AND THE COURT OF LAW REGARDING COMPENSATION IN PUBLIC SERVICE DISPUTE - Bimasakti, Muhammad Adiguna (Jurnal Hukum dan Peradilan, 2021)
Public Service is the embodiment of the main tasks of a governance. But in its implementation sometimes it also causes disputes due to losses experienced by community members due to a bad public service. Therefore Law No. 25 of 2009 concerning Public Services regulates dispute resolution in the implementation of public services. At least there are two types of ways to resolve compensation in public service dispute that caused by Tort in the Public Service, namely the Non-Litigation settlement through the Ombudsman, and the Litigation settlement through the Court. However, in further studies it was found that there was an overlap of authority between the Ombudsman and the Court in resolving public service disputes. This paper will try to discuss this in depth in terms of the philosophy of the existence of the Ombudsman, and its implications for its Special Adjudication authority. Aside from that, this paper will also discusses about the procedure of proceedings in the Administrative Court regarding public service disputes.